Thermal barrier coating with high bonding strength and flame thermal shock resistance and preparation method thereof
By introducing a ceramic transition layer into the thermal barrier coating and using Nano-8YSZ and rare earth tantalate materials, the existing thermal barrier coatings have been solved, and the existing thermal barrier coatings with low bonding strength and short service life under high-temperature flame impact conditions are achieved, and the thermal barrier coating with high bonding strength and flame thermal shock resistance is achieved, meeting the high performance needs in aerospace and other fields.
Patent Information
- Application Number
- CN202411855464.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
The existing thermal barrier coatings have low bond strength and short service life under high-temperature flame impact conditions, making it difficult to meet the demand for high-performance thermal barrier coatings in aerospace and other fields.
The ceramic transition layer is used between the metal bonding layer and the ceramic surface layer, and the ceramic surface layer is prepared by atmospheric plasma spraying technology. Combining Nano-8YSZ and rare earth tantalate materials, a thermal barrier coating with high binding strength and flame thermal shock resistance is designed.
It significantly improves the bonding strength of the thermal barrier coating and resists heat shock performance of 1400℃, extends the service life of the coating, and meets the demand for high-performance thermal barrier coatings in the fields of aerospace and other fields.
Smart Images

Figure CN119663161A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ultra-high temperature thermal barrier coatings used for surface protection of hot end components such as aircraft engines, ground heavy gas turbines and hypersonic aircraft, and specifically relates to a thermal barrier coating with high bonding strength and flame thermal shock resistance and a preparation method thereof. Background Art
[0002] Surface coating technology is an important component of aerospace manufacturing technology. Thermal barrier coatings (TBCs) use ceramic materials with high melting point, low thermal conductivity and high strength, which play a vital role in the high-temperature service protection of single-crystal alloy blades of turbine engines. The so-called TBCs refers to a metal bonding layer (BC) with strong oxidation resistance and a ceramic surface layer (TC) with good thermal insulation and long heat resistance. It is mainly used to reduce the working temperature of the alloy matrix to avoid high-temperature oxidation, corrosion and wear.
[0003] The structural design of TBCs needs to take into account that the prepared coating structure has low thermal conductivity, high bonding strength and high temperature flame thermal shock resistance; the preparation technology of TC layer mainly includes atmospheric plasma spraying (APS) and electron beam physical vapor deposition (EB-PVD); the BC layer mainly adopts supersonic flame spraying (HOVF) technology; among them, APS process is simple, deposition efficiency is high and cost is low, the sprayed YSZ coating has loose and porous characteristics, and the porosity is generally controlled at 10% to 15%; the existence of these pore structures in TC makes the coating have good performance in thermal insulation and effective The strain tolerance of the coating can be adjusted during high-temperature service; however, some microcracks, pores and other defects at the TC / BC interface will lead to low elastic modulus and poor adhesion of the coating, so the bonding strength of the YSZ coating under APS is generally lower than 35MPa, and the service life is short under high-temperature flame impact conditions in actual service; compared with traditional YSZ materials, rare earth tantalate materials have ferroelastic phase transitions and will form ferroelastic domains at high temperatures, which play a stress buffering role when loading and releasing stress, greatly improving the high-temperature fracture toughness of the material, so they have great application prospects in the field of TBCs. Summary of the invention
[0004] The purpose of the present invention is to provide a thermal barrier coating with high bonding strength and flame thermal shock resistance and a preparation method thereof, so that TBCs can have a large strain tolerance and higher bonding strength, and further improve their high-temperature flame thermal shock resistance. This will be conducive to achieving long-life performance of TBCs in ultra-high temperature (thermal / mechanical / chemical) coupled service environments, so as to meet the increasingly stringent requirements of aerospace and other fields for current and future higher performance TBCs.
[0005] The present invention adopts the following technical scheme to achieve the above-mentioned purpose: A thermal barrier coating with high bonding strength and flame thermal shock resistance, the thermal barrier coating has a metal bonding layer and a ceramic surface layer; the thermal barrier coating is also provided with a ceramic transition layer between the metal bonding layer and the ceramic surface layer; the thickness of the ceramic transition layer is 40-60 μm, and the porosity is less than 5%; the thickness of the metal bonding layer is 100-150 μm, and the porosity is less than 1%. The ceramic surface layer adopts a structure in which unmelted particle agglomerates are embedded and a typical laminar structure coexists; the thickness of the ceramic surface layer is 180-250 μm, the porosity is 5%-15%, and the content of unmelted particle agglomerates is 5%-10%.
[0006] The powder used for the metal bonding layer is MCrAlY or MCrAlYTa, M is Fe, Co, Ni or Ni+Co, and the particle size range is 5 to 38 μm.
[0007] The powders used for the ceramic surface layer and the ceramic transition layer are one or more of nano-yttria partially stabilized zirconia (YSZ), rare earth tantalate materials, etc., and the particle sizes range from 30 to 100 μm and 50 to 100 μm respectively.
[0008] A method for preparing a thermal barrier coating with high bonding strength and flame thermal shock resistance, the preparation method comprising the following steps: S1, using 80-120 mesh white corundum powder to sandblast the surface of the nickel-based high-temperature alloy substrate to enhance the surface roughness (>6μm) and perform ultrasonic cleaning and drying; S2, spraying a metal bonding layer on the surface of the nickel-based high-temperature alloy substrate after sandblasting and preheating treatment by using HOVF technology; the bonding layer is prepared by supersonic flame spraying technology; during the preparation of the metal bonding layer, the oxygen flow rate is 1800-1900 SCFH, the carrier gas nitrogen flow rate is 20-30 SCFH, the aviation kerosene flow rate is 5-10 GPH, the powder feeding amount is 10-30 g / min, the horizontal movement speed of the spray gun is 300-800 mm / s, and the spraying distance between the spray gun and the metal substrate surface is 300-500 mm; S3, mixing nano-YSZ and rare earth tantalate uniformly, heating and accelerating them through the high-temperature flame flow of APS, and then impacting them on the surface of the metal bonding layer to form a dense ceramic transition layer; S4, based on the above structure, APS technology is used to deposit a layer of 8YSZ ceramic surface layer with embedded unmelted particle agglomerates and typical laminar structure; during the preparation of the ceramic transition layer and the ceramic surface layer, the voltage is 350-420V, the current is 350-420A, the carrier gas argon flow rate is 30-50SCFH, the powder feeding amount is 10-30g / min, the horizontal movement speed of the spray gun is 300-800mm / s, the spraying distance between the spray gun and the metal substrate surface is 80-130mm, and the substrate temperature is 300-500℃.
[0009] The ceramic transition layer and the ceramic surface layer are prepared by atmospheric plasma spraying technology.
[0010] The molar ratio of the nano-YSZ and the rare earth tantalate powder is 1:3 to 3:1.
[0011] The thermal barrier coating with high bonding strength and resistance to 1400° C. flame thermal shock according to the present invention is suitable for the surfaces of hot end components of aircraft engines, ground heavy gas turbines, hypersonic aircraft, etc.
[0012] According to the thermal barrier coating of the present invention, the ceramic transition layer structure design at the TC / BC bonding part improves the key problem of weak mechanical bonding at the interface of conventional layered structure TBCs. According to the TBCs preparation method of the present invention, the design flexibility is high and the process cost is low, and the TBCs multilayer structure can be efficiently regulated in actual industrial applications. In addition, the content of the present invention uses simple and economical process control measures to improve the mutual constraints between the high mechanical bonding of densification and the high strain tolerance of loose porous thermal insulation at the interface, thereby realizing the coordinated TBCs structural design of low thermal conductivity, high combined strength, and resistance to high-temperature flame thermal shock, providing an effective idea and method for solving the above-mentioned TBCs long life technical barriers. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Schematic diagram of the preparation process flow of thermal barrier coatings with low thermal conductivity, high bonding strength and high temperature flame and thermal shock resistance on a nickel-based high-temperature alloy substrate.
[0014] Figure 2 NiCoCrAlYTa material for metal bonding layer and ceramic layer in thermal spraying process Nano -8YSZ and rare earth tantalate materials. Among them, NiCoCrAlYTa, Nano -8YSZ and rare earth tantalate powder d 90 They are 38.5μm, 85.6μm and 69.9μm respectively, and the particle size range meets the requirements of thermal spraying process.
[0015] Figure 3These are scanning electron microscope (SEM) photos of thermal barrier coatings with and without transition layers. The thickness of the metal bonding layer is 100-150μm, and the porosity is <1%; the thickness of the ceramic transition layer is 40-60μm, and the porosity is <5%; the thickness of the ceramic surface layer is 180-250μm, the porosity is 5%-15%, and the content of unmelted particle agglomerates is 5%-10%.
[0016] Figure 4 The following is a comparison of the bonding strength of thermal barrier coatings with and without transition layers. After adding a ceramic transition layer with a thickness of 40-60 μm, the average bonding strength of the coating can reach 41.1 MPa, while the average bonding strength of TBCs without a transition layer is less than 35 MPa.
[0017] Figure 5 This is a comparison chart of the 1400℃ flame thermal shock cycle life of thermal barrier coatings with and without transition layers.
[0018] Figure 6 This is a comparison of the macroscopic failure evolution process of the sample surface during the 1400℃ flame thermal shock test of thermal barrier coatings with and without transition layers. The TBCs with transition layers began to peel off at the chamfer after 2600 thermal shock cycles, and there was no obvious peeling on the sample surface after 3862 cycles. However, the TBCs without transition layers began to peel off at the chamfer after 804 thermal shock cycles, and the peeling area on the sample surface reached 5% after 3245 cycles. The structural design of the ceramic transition layer in TBCs significantly improves the bonding strength and resistance to 1400℃ flame thermal shock of the coating. DETAILED DESCRIPTION
[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that the content of the present invention is not limited to the technical content involved in the embodiments.
[0020] like Figure 1 As shown, the thermal barrier coating with high bonding strength and 1400° C. flame thermal shock resistance according to the present invention comprises a nickel-based high-temperature alloy substrate at the bottom layer.
[0021] The thermal barrier coating with high bonding strength and 1400°C flame thermal shock resistance according to the present invention comprises a metal bonding layer bonded to a nickel-based high-temperature alloy substrate. In a preferred embodiment, the material of the metal bonding layer is NiCoCrAlYTa, with a thickness of 100-150 μm and a porosity of <1%.
[0022] In a preferred embodiment, the thickness of the ceramic transition layer is 40-60 μm, and the porosity is less than 5%.
[0023] In a preferred embodiment, the thickness of the ceramic surface layer is 180-250 μm, the porosity is 5%-15%, and the content of unmelted particle agglomerates is 5%-10%. Embodiment 1:
[0024] The material used for the nickel-based high-temperature alloy substrate is Hastelloy X, and the size is processed into Φ25.0mm×6.0mm, and the edge of the substrate is chamfered with R1.0mm. First, the surface of the nickel-based high-temperature alloy substrate is sandblasted, and the sandblasting material is 80 mesh white corundum.
[0025] The HOVF technology is used to deposit a metal bonding layer on the surface of the nickel-based high-temperature alloy substrate after sandblasting. The material used for the metal bonding layer is NiCoCrAlYTa, and the particle size range is 5 to 38 μm. Figure 2 (a). First, the surface of the nickel-based high-temperature alloy substrate is preheated using the HOVF technology, and the preheating temperature is 200-300°C. During the deposition of the metal bonding layer, the oxygen flow rate is 1850 SCFH, the carrier gas nitrogen flow rate is 23 SCFH, the aviation kerosene flow rate is 7 GPH, the powder feeding amount is 10 g / min, the horizontal movement speed of the spray gun is 500 mm / s, and the spraying distance between the spray gun and the surface of the Hastelloy X substrate is 350 mm.
[0026] APS technology is used to deposit a ceramic transition layer on the surface of the metal bonding layer. The material used for the ceramic transition layer is Nano -8YSZ and rare earth tantalate 1:1 (molar ratio) mixed powder, Nano The particle sizes of -8YSZ and rare earth tantalates range from 30 to 100 μm and 50 to 100 μm, respectively. Figure 2 (b) and (c). During the deposition of the ceramic transition layer, the voltage was 420 V, the current was 420 A, the carrier gas argon flow rate was 40 SCFH, the powder feeding amount was 10 g / min, the horizontal movement speed of the spray gun was 300 mm / s, the spraying distance between the spray gun and the surface of the Hastelloy X substrate was 115 mm, and the substrate temperature was 300-500 °C.
[0027] APS technology is used to deposit a ceramic surface layer on the basis of the ceramic transition layer. The material used for the ceramic surface layer is Nano -8YSZ, Nano The particle size range of -8YSZ is 30 to 100 μm. During the deposition of the ceramic surface layer, the voltage is 420 V, the current is 420 A, the carrier gas argon flow rate is 40 SCFH, the powder feeding amount is 10 g / min, the horizontal moving speed of the spray gun is 300 mm / s, the spraying distance between the spray gun and the surface of the Hastelloy X substrate is 115 mm, and the substrate temperature is 300 to 500 ° C.
[0028] like Figure 3 As shown in (a), the prepared TBCs have obvious microstructural characteristics, forming a dense layer at the junction of the ceramic surface layer and the metal bonding layer. Nano -8YSZ and rare earth tantalate mixed ceramic transition layer, and the ceramic surface layer has a high content of unmelted particle agglomerates embedded and a typical laminar structure.
[0029] Comparative Example 1: The difference between this comparative example and Example 1 is that there is no ceramic transition layer in the TBCs structural design. The microstructure of the coating prepared in Comparative Example 1 is as follows Figure 3 As shown in (b), there are structural features of unmelted particle agglomerates embedded and pores (microcracks, pores, etc.) at the bonding site of the TC / BC interface. Embodiment 2:
[0030] According to Example 1, an APS thermal barrier coating with a transition layer was prepared, and the bonding strength of the two coatings was tested according to the comparative example 1 without a transition layer and the thermal barrier coating of Example 1 with a transition layer.
[0031] The specific steps are as follows: According to GB / T 8642-2002, the bonding strength of the coating is measured by the dual tensile method. The specific test process is as follows: Use FMOR1000 adhesive film to bond the coating sample to two stainless steel tensile columns, place it in an electric blast drying oven and heat it to 190°C, keep it warm for 4 hours, and cool it to room temperature. After the curing is completed, the dual parts of the bonding coating sample are fixed on a microcomputer-controlled electronic universal testing machine. The computer control system used for the operation accurately controls the test conditions, and the tensile rate is set to 10mm / min. Then, the load is evenly loaded until the coating in the dual parts is debonded. The computer control system automatically records the maximum destructive load at the moment of debonding. Each group of samples is repeated 3 times, and the average value is finally taken to evaluate the bonding strength of the coating to reduce errors.
[0032] like Figure 4 As shown, the APS thermal barrier coating of the dense ceramic transition layer prepared in Example 1 has a high bonding strength, which can reach an average of 41.1 MPa; the average bonding strength of Comparative Example 1 is only 28.8 MPa. Embodiment 3:
[0033] According to Example 1, an APS thermal barrier coating with a transition layer was prepared, and the two coatings were subjected to a 1400° C. flame thermal shock test according to Comparative Example 1 without a transition layer and Example 1 with a transition layer.
[0034] The specific steps are: fix the coating sample on the thermal shock test device with a test piece fixture, use oxygen as the combustion-supporting gas and propane as the fuel, and burn through a circular flame heating system to obtain a stable high-temperature flame spray gun flame flow with high temperature and high speed. The specific test conditions are: the oxygen pressure after decompression is 0.3MPa, the gas pressure after pressurization is 0.15MPa, and the flame flow speed is 0.5 Mach. During the test, an infrared temperature measuring device is used to monitor the temperature changes on the surface of the coating sample. The surface temperature of the sample needs to be rapidly increased to 1350℃~1400℃ within 20S and kept warm in this temperature range. After that, an air cooling device is used to provide compressed air directly blown to the front of the coating sample for cooling for 15S. This heating-cooling process is regarded as one cycle. When the peeling area on the surface of the coating sample reaches 5%, it is regarded as a failure.
[0035] like Figure 5 As shown in FIG. 1 , the APS thermal barrier coating with a transition layer prepared in Example 1 has a relatively high thermal shock cycle life. When the cycle life reaches 3862 times, there is no obvious peeling on the surface of the coating sample, and the thermal shock begins to peel off at the chamfer after 2600 times (as shown in FIG. Figure 6 As shown); when the number of thermal shock cycles of the APS thermal barrier coating without a transition layer prepared in Comparative Example 1 reached 3245 times, the peeling area of its surface coating was 3.85%, and it only began to peel off at the chamfer after 804 times.
[0036] The above-mentioned results show that the present invention provides a thermal barrier coating with high bonding strength and resistance to 1400°C flame thermal shock and its preparation method based on HVOF and APS technology. By depositing a layer of 40-60 μm thick between the metal bonding layer and the ceramic surface layer, Nano The dense ceramic transition layer of 1:1 (molar ratio) mixture of -8YSZ and rare earth tantalate effectively enhances the mechanical bonding at the TC / BC interface and further improves the flame thermal shock resistance of TBCs under the service temperature of 1400℃.
[0037] The above content is only to further illustrate the design content and implementation plan of the present invention, and cannot be used to limit the protection scope of the present invention. All modifications or replacements made in accordance with the design content and implementation plan proposed by the present invention are required to fall within the protection scope of the present invention.
Claims
1. A thermal barrier coating with high bonding strength and flame thermal shock resistance, the thermal barrier coating having a metal bonding layer and a ceramic surface layer; characterized in that: The thermal barrier coating is also provided with a ceramic transition layer between the metal bonding layer and the ceramic surface layer; the thickness of the ceramic transition layer is 40-60 μm, and the porosity is less than 5%; the thickness of the metal bonding layer is 100-150 μm, and the porosity is less than 1%. The ceramic surface layer adopts a structure in which unmelted particle agglomerates are embedded and a typical laminar structure coexists; the thickness of the ceramic surface layer is 180-250 μm, the porosity is 5%-15%, and the content of unmelted particle agglomerates is 5%-10%.
2. A thermal barrier coating with high bonding strength and flame thermal shock resistance as claimed in claim 1, characterized in that: The powder used for the metal bonding layer is MCrAlY or MCrAlYTa, M is Fe, Co, Ni or Ni+Co, and the particle size range is 5 to 38 μm.
3. A thermal barrier coating with high bonding strength and flame thermal shock resistance as claimed in claim 1, characterized in that: The powders used for the ceramic surface layer and the ceramic transition layer are one or more of nano-yttria partially stabilized zirconium oxide, rare earth tantalate materials, etc., and the particle sizes range from 30 to 100 μm and 50 to 100 μm respectively.
4. A method for preparing a thermal barrier coating with high bonding strength and flame thermal shock resistance according to any one of claims 1 to 3, characterized in that: The preparation method The following steps are involved: S1, using 80-120 mesh white corundum powder to sandblast the surface of the nickel-based high-temperature alloy substrate to enhance the surface roughness (>6μm) and perform ultrasonic cleaning and drying; S2, spraying a metal bonding layer on the surface of the nickel-based high-temperature alloy substrate after sandblasting and preheating treatment by using HOVF technology; the bonding layer is prepared by supersonic flame spraying technology; during the preparation of the metal bonding layer, the oxygen flow rate is 1800-1900 SCFH, the carrier gas nitrogen flow rate is 20-30 SCFH, the aviation kerosene flow rate is 5-10 GPH, the powder feeding amount is 10-30 g / min, the horizontal movement speed of the spray gun is 300-800 mm / s, and the spraying distance between the spray gun and the metal substrate surface is 300-500 mm; S3, mixing nano-YSZ and rare earth tantalate uniformly, heating and accelerating them through the high-temperature flame flow of APS, and then impacting them on the surface of the metal bonding layer to form a dense ceramic transition layer; S4, based on the above structure, APS technology is used to deposit a layer of 8YSZ ceramic surface layer with embedded unmelted particle agglomerates and typical laminar structure; during the preparation of the ceramic transition layer and the ceramic surface layer, the voltage is 350-420V, the current is 350-420A, the carrier gas argon flow rate is 30-50SCFH, the powder feeding amount is 10-30g / min, the horizontal movement speed of the spray gun is 300-800mm / s, the spraying distance between the spray gun and the metal substrate surface is 80-130mm, and the substrate temperature is 300-500℃.
5. The method for preparing a thermal barrier coating with high bonding strength and flame thermal shock resistance according to claim 4, characterized in that: The ceramic transition layer and the ceramic surface layer are prepared by atmospheric plasma spraying technology.
6. The method for preparing a thermal barrier coating with high bonding strength and flame thermal shock resistance according to claim 4, characterized in that: The molar ratio of the nano-YSZ and the rare earth tantalate powder is 1:3 to 3:1.